2010
DOI: 10.1111/j.1439-0442.1975.tb01465.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Diazinon on the Gonads of Fowls

Abstract: Summary The occurrence of reproductive disturbances in a flock of laying hens dipped in a high concentration of Diazinon suggested a study of the effect of this insecticide on the gonads of the fowl. The levels of gonadotrophic, thyrotrophic and adrenocorticotrophic hormones in the pituitary and serum of the treated hens were significantly lower than in control birds. A causal relationship between these low levels and the extensive retrogressive changes observed grossly and microscopically in the ovaries of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…flocks reported single infection (11.76%), one with M. gallisepticum and one with E. coli while mixed infection recorded in 14 farms, 82.35% (100% of each White Nicholas and Bronze and 50% of Balady flocks). from the field surveyed results, E. coli and M. gallisepticum were identified either alone or together with other bacteria, so they might be responsible for turkeys' sinusitis while M. meleagridis and ORT were not identified alone, also E. coli, M. gallisepticum, and ORT were more frequently mixed with each other than M. meleagridis, these results matched with those of Abd El-Hameed et al (2009) who detected M. gallisepticum, either alone or coupled with other pathogens (P. multocida and E. coli) was the predominant etiologic agent responsible for the respiratory problems including infra-orbital sinusitis of the infected turkey flocks,Sokkar et al (1986) identified M. gallisepticum and M. meleagridis either alone or mixed with E. coli, P. aeruginosa, S. aureus and S. gallinarun pullorum from turkeys located in different areas of Upper Egypt. Abd El-Rahman (1995) determined serologically M. gallisepticum, M. meleagridis, M. synoviae, and M. Iowa and concluded that M. gallisepticum was the predominant detected mycoplasmas, 90 % of the examined turkeys' flocks referring to the spread of M. gallisepticum rather than M. meleagridis among turkey's farms.Sokker et al (1986);KeBin (2003) andMoustafa (2005) were naturally and experimentally reported synergistic action between M. gallisepticum and E. coli either alone or associated with other pathogens as a major etiologic agents responsible for swollen head syndrome in turkeys, chickens and ostriches.…”
supporting
confidence: 81%
“…flocks reported single infection (11.76%), one with M. gallisepticum and one with E. coli while mixed infection recorded in 14 farms, 82.35% (100% of each White Nicholas and Bronze and 50% of Balady flocks). from the field surveyed results, E. coli and M. gallisepticum were identified either alone or together with other bacteria, so they might be responsible for turkeys' sinusitis while M. meleagridis and ORT were not identified alone, also E. coli, M. gallisepticum, and ORT were more frequently mixed with each other than M. meleagridis, these results matched with those of Abd El-Hameed et al (2009) who detected M. gallisepticum, either alone or coupled with other pathogens (P. multocida and E. coli) was the predominant etiologic agent responsible for the respiratory problems including infra-orbital sinusitis of the infected turkey flocks,Sokkar et al (1986) identified M. gallisepticum and M. meleagridis either alone or mixed with E. coli, P. aeruginosa, S. aureus and S. gallinarun pullorum from turkeys located in different areas of Upper Egypt. Abd El-Rahman (1995) determined serologically M. gallisepticum, M. meleagridis, M. synoviae, and M. Iowa and concluded that M. gallisepticum was the predominant detected mycoplasmas, 90 % of the examined turkeys' flocks referring to the spread of M. gallisepticum rather than M. meleagridis among turkey's farms.Sokker et al (1986);KeBin (2003) andMoustafa (2005) were naturally and experimentally reported synergistic action between M. gallisepticum and E. coli either alone or associated with other pathogens as a major etiologic agents responsible for swollen head syndrome in turkeys, chickens and ostriches.…”
supporting
confidence: 81%